Annotated record of the detailed examination of Mn deposits from DSDP Leg 31 (Holes 290, 291, 294, 295, 297, 299, 300, 300A, 301, 302) - James C Ingle; Daniel E Karig; D E Bouma; C Howard Ellis; N S Haile; I Koizumi; J Casey Moore; H Ujiie; T Watanabe; S M White; M Yasuii; Hsin Yi Ling (PANGAEA, 1975)
The major purpose of Leg 31 was the scrutiny of tectonic, sedimentologic, volcanic, paleontologic, and paleooceanographic processes operative in arc-marginal basin complexes along with a deciphering of basin history. The 12 sites ultimately occupied during Leg 31 all yielded significant new data bearing on the nature and evolution of the West Philippine Basin, Shikoku Basin, and Sea of Japan. The major objective at sites 290 through 292 was to test the mode and age of origin of the West Philippine Sea with emphasis on the nature of the Central Basin Fault. Sites 294/295 were drilled far to the east of the Central Basin Fault zone in the thin sediment blanket covering deeper portions of the northeastern West Philippine Basin. The other sites were situated in the Sea of Japan.
Supplement to: Ingle, JC et al. (1975): Initial Reports of the Deep Sea Drilling Project. U. S. Government Printing Office, XXXI, 927 pp, https://doi.org/10.2973/dsdp.proc.31.1975